Análise de padronização em dimensões de blocos de concreto fabricados na cidade de Campo Mourão - PR - Silva, Jorge Alexandre Humeniuk da (2013)
The use of concrete blocks for the execution of masonry or brickwork simple closure, is increasingly used in the city and in regions near Campo Mourão - PR because their use enables buildings with shorter lead times and less waste, but is of great importance to this material compliance with current regulations, because the contrary can lead to final results in unwanted buildings, even with that amount which covers the improvement and studies of modular masonry units, there is little research on this topic. Thus this research seeks information about the compliance of concrete blocks manufactured in Campo Mourão - PR, simply and clearly, seeking information about what rules the manufacturing of this material with respect to dimensions, and if these are met by companies manufacturers of concrete blocks, besides dealing with matters concerning the production of this material and some differential production, resulting in a final product with better compliance.